Evaluation of dicyandiamide treated urea and organic manure on nitrous oxide emission, nitrogen uptake and yield of rice grown on acid sulphate soil - Shamsuzzaman, S. M. (2015)
Rice soil is a major source of nitrous oxide (N2O), and the application of N as inorganic and/or organic is an important factor affecting N2O emissions. The nitrification inhibitor (NI), dicyandiamide (DCD) is effective in suppressing nitrification and N2O emission. Therefore, the purpose of this study was to find out a feasible fertilization practice including DCD and organic manure (OM) for reducing N2O emission with better yield and soil health of acid sulphate soil. An incubation study was conducted to observe the impacts of DCD with OM and urea on N dynamics and N2O emission from acid sulphate soil. The experiment was conducted with two-level factorial: seven N sources and two NI levels. After 30 days of incubation, the mineral-N (NH4 + + NO3 -) was highest (255.07 μg g-1) for DCD with oil palm compost (OPC) + urea. The highest net N-mineralization (213.07 μg g-1) was recorded for DCD with urea and net nitrification (16.26 μg g-1) was recorded for urea alone, but the highest cumulative N2O emission (5.46 μg g-1) was in poultry dung (PD) + urea. In addition, DCD could effectively inhibit net N nitrification and N2O emission (22.01-32.40%). A glasshouse experiment was conducted to investigate the effects of DCD with OM and urea on yield of MR219 rice and N2O emission from acid sulphate soil. The experiment used a two-level factorial with four N sources and two NI levels. Nitrogen source and DCD interaction significantly increased the grain yield of rice (4.76-21.95%) compared to urea alone. The combined application of DCD with OPC + urea was most effective in a higher grain yield (22.81 g/hill), nutrient uptake; N (631.64 g/hill), P (234.79 g/hill), K (651.01 g/hill), and S (87.95 g/hill) followed by DCD with PD + urea. Seasonal peaks of N2O flux occurred 3rd - 10th day after urea fertilization during the rice growing season with the value of 319.84-424.63 μm m-2 h-1. Cumulative N2O emission (CNE) during rice growth season was 3.10-3.63 kg N2O-N ha-1 for N source and application of DCD decreased the CNE by 21.97-27.07%, respectively. A field experiment was conducted at Semerak, Kelantan, Malaysia to evaluate the influence of DCD with OM and urea on N2O emission from MR 219 rice field and fertility of acid sulphate soil. The experimental design was similar to glasshouse experiment. The highest grain yield increase (31.62%) and total uptake of N (164.79 kg ha-1), P (55.42 kg ha-1), K (153.28 kg ha-1), and S (21.88 kg ha-1) was obtained for the application of DCD with OPC + urea followed by DCD with PD + urea. The trend of seasonal peaks of N2O flux was similar to glasshouse, but the values were 347.65-456.60 μm m-2 h-1 for the N source. Cumulative N2O emission during rice growth season was 3.27- 3.83 kg N2O-N ha-1 for N source. Application DCD decreased the CNE by 15.72-24.72 %. Soil pH, organic carbon, and soil primary- (N, P and K), secondary- (Ca, Mg and S) and micro-nutrient (Zn, Cu, Fe and Mn) were significantly influenced by N source only following the order of OPC + urea-N ≥ PD + urea-N > rice straw + urea-N > urea-N (control). Finally, the integrated use of DCD with OPC and urea was more effective in reducing N2O emissions with improving rice yield and soil health. Hence, combination of 13.5 kg ha-1 (15% of applied N) DCD with 1.8 t ha-1 (30% N of recommended dose) OPC and 90 kg ha-1 (75% N of recommended dose) urea may be the most potential combination to reduce N2O emission, improve rice yield and health of acid sulphate soil in Malaysia.